Ethological Observations on the Sloth Bear (Melursus ursinus) - Gopal, Rajesh (Indian Forester, 1991)
The paper highlights some ethological observations on the Sloth bear (Melursus ursinus) which is an important endemic, omnivore of our tropical ecosystem, adapted to exploit the myrmecophagus niche. The seasonal food preference, group composition, breeding, mother-young relationship and response to other species have also been indicated.